COMPARISON OF CONVENTIONAL METHOD, RADIOMETRIC METHOD AND METHOD USING OXIDATION-REDUCTION DYE FOR DETECTION OF MULTI DRUG RESISTANT TUBERCULOSIS - Vaidya, Shashikant; Sharma, Jaishankar; Muley, Shreyasi; Koppikar, Geeta; Kulkarni, Mohan; Chowdhary, Abhay (LIFE: International Journal of Health and Life-Sciences, 2015)
Today Tuberculosis (TB) has become the most important communicable disease in the world. The emergence of multidrug resistant (MDR) TB has become the main threat to TB treatment and control programs. Rapid detection of TB is critical for the effective treatment of patients. Recently, a method using the Oxidation - Reduction dye has been proposed for drug susceptibility testing of Mycobacterium tuberculosis (M.tuberculosis). In the present study, we have compared Drug Susceptibility Testing (DST) by conventional method, Radiometricmethod like BACTEC460TB (B460TB) System and Oxidation-Reduction Assay such as Microplate Alamar Blue Assay (MABA) for detection of MDR TB. Total 60 clinical isolates of M.tuberculosis were included in the study. The results obtained by MABA for DST of M.tuberculosis were compared with those obtained by B460TB system and Conventional method. DST results obtained by MABA showed good agreement with results obtained by B460TBsystem and Conventional method for Isoniazid and Rifampicin. In our study specificity and sensitivity for susceptible and resistant strain was found to be 98% and 100% for Rifampicin respectively and 100% and 95% for Isoniazid respectively for MABA.MABA appears to be a reliable method for the rapid and simultaneous detection of MDR-TB and DST of M. tuberculosis. It is simple and inexpensive method for DST of M.Tuberculosis with minimal biohazard risk.